Role of Indian Judiciary in Ensuring Good Governance: A Comparative Analysis of South Asian Countries - Noman Ali Shah; Prof. Dr. Aatir Rizvi; Dr. Kashif Javed (Research Journal of Psychology, 2025)
Good governance is a primary principal for the rule of law in any democratic society. Good governance constitutes fairness, accountability and transparency in the functioning of the different institutions of the government. Political and social stability of any state totally depends on its governance. There are many governance challenges all over the world and specifically in the South Asian countries such as corruption, political interference, lack of accountability, abuse of merit policy and mismanagement by the government officials. Judiciary plays an important role in promoting and maintaining good governance in any country. Being an important organ of a government, judiciary takes full responsibility to provide basic and fundamental rights to the citizens. In South Asian countries where judiciary faces many challenges to uphold its position as the guardian and custodian of the constitutional and fundamental rights, Indian judiciary has established many precedents for ensuring good governance mechanism in the country. This study investigates the role of the judiciary in South Asia in respect of promoting good governance with special attention to India and comparative analysis from Pakistan, Bangladesh, Sri Lanka and Nepal. It is found that the judiciary shall perform its duties without any pressure, partiality and biasness to promote good governance. Judicial Activism can be used as a successful tool for governance reforms.